A vida sensível do mito na literatura Huni Ku - Rafael Castro de Souza (2017)
This dissertation aims to delineate a reading of the emerging literature of the Huni Ku people, guided by the approximation between what is traditionally called the myth and the sensible experience. As a main theoretical foundation, we propose a cross between certain aspects of Lévi-Strausss thought - expressed mainly in Mythologiques - and the propositions of the philosopher Emanuele Coccia on the nature of the sensible, aspect of life (human, fauna and flora) historically neglected by philosophy. We read some of the pieces of this literature - narratives and chants - in an attempt to demonstrate, from its immanent elements and extra-textual aspects, that it is precisely the presence of sensible experience in the treatment of myths the main substrate and touchstone of this true literature. To this phenomenon that characterizes the textualities of this forest people, we gave the name sensible life of the myth.